Pengaruh Proporsi Komisaris Independen, Ukuran Komite Audit dan Ukuran Perusahaan Terhadap Siklus Konversi Kas - Muthia Rahmadani Sadono (Akuntabilitas, 2016)
This research aims to analyze and get empirical evidence about the effect of independent commissioner, audit committee and firm size on cash conversion cycle. Independent commissioner was measured by proportion of independent commissioner to board of commissioner, audit committee was measured by size of audit committee, and firm size was measured by logaritma natural of total revenue (LnTR). Sample of this research were consumer goods industry companies which were listed in Indonesia Stock Exchange (IDX) during 2013-2015 period. The number of manufacturing companies in this study were 33 companies with 3 years observation that acquired by using purposive sampling method. Hypothesis in this research were tested by multiple regression model. The results of this research showed that independent commissioner and audit committee not significantly influence on cash conversion cycle. In the other hand, firm size had significant negatively influence on cash conversion cycle.